IMPLEMENTASI KEBIJAKAN PUBLIK BERBASIS DIGITAL DI KECAMATAN BUKIT RAYA KOTA PEKANBARU PADA TAHUN 2017-2019 - Marvia Swesty; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The implementation of digital-based public policies has been stated in Pekanbaru Mayor Regulation Number 273 of 2017 concerning the Integrated Administration Service System in Pekanbaru  City District. This digital-based service has created several uses, namely: increasing efficiency, improving effectiveness, and improving service quality. Bukit Raya District is a sub-district located in Pekanbaru, Riau Province, which improves public services by using the concept of E-Government. Innovations created using a digital system in the form of mobile application products. This is useful in helping the city government of Pekanbaru in realizing the vision of the city of Pekanbaru, which is to make the city of Pekanbaru a "Smart City Madani".This study aims to see the implementation of public policies of the Bukit Raya District government in improving public services by using a digital system in accordance with the Pekanbaru Mayor Regulation. The theory used in this research is Policy Implementation theory and E-Government theory. This research uses descriptive method with qualitative research type. The types of data used in this study are primary and secondary data obtained through direct interviews with informants, documentation and observation.Bukit Raya District has implemented digital-based services since 2017 until now. So far, the digital service policy in Bukit Raya District has been running well. From the application of technology-based service policies, it can help realize the vision of the city of Pekanbaru, namely to make the city of Pekanbaru a "Smart City Madani". However, in implementing digital-based service policies in Bukit Raya District, there are obstacles faced, namely human resource management in Bukit Raya District is still lacking, especially in terms of skills / abilities possessed to run a digital service system as well as factors from the educational background of employees. As well as the facilities and infrastructure needed are still not fulfilled to carry out these digital services. From this research, it is suggested that the role of city government should be more focused on developing public services with digital systems. Keyword: Implementation, Public Service, E-Government, Innovation